Effects of seed potato maturity, weight and treatments for breaking dormancy on potato yield (Solanum tuberosum L.) cultivar Itararé (IAC 5986) - Pógi, Maria Cristina; Brinholi, Oswaldo (Pesquisa Agropecuaria Brasileira, 1995)
The effects of seed potato maturity, weight and treatments for breaking dormancy were studied on tuber sprouting, plant development and yield of potato cultivar Itararé (IAC 5986). Two types of seed originated from precocious and normal harvesting and classified by weight (less than 30g; from 30 to 60g and larger than 60g) were submitted to the following treatments for breaking dormancy: GA (10 ppm/10 minutes); CS2 (30 cc/m3/48 hours); CS2 (30 cc/m3/48 hours) plus GA (10 ppm/10 minutes); and cold tuber storage for 60 and 90 days. Seeds from different treatments and a control were planted in November, after sprouts had reached 10mm in height. It is concluded that: seed potato maturity influenced sprouting, emergence and yield. Potato weight influenced sprouting, number of sprouts, number of branches and yield; and treatments for breaking dormancy influenced starting of sprouting, number of sprouts, total emergence and yield.